Improving Social Skills of Elementary School Students by Using Umma Kalada's Indigenous Knowledge on Social Studies Topics - Heronimus Delu Pingge; Nana Supriatna; Sapriya; Abdul Azis Wahab (Universitas Pendidikan Ganesha, 2023)
Students show non-cooperative attitudes, ridicule each other among students, do not listen to each other in group work and do not queue to collect assignments. It is what underlies this research. The local wisdom of the Umma Kalada, the indigenous people of Loura, contains the value of social skills as a guide to help students who are still weak in developing relationships with others. In order to improve the social skills of Class IVa SDK (Catholic Elementary School) students through applying Umma Kalada values. This study aims to analyze the value of social skills in Umma Kalada's local wisdom. The research design used was qualitative research using the collection action research method developed by Kemmis and Taggart. Action research was conducted in three cycles. Data collection techniques using non-test techniques and tests in the form of observation, learning achievement tests and interviews. The collected data is described, and conclusions are drawn. The results of this study found that applying Umma Kalada's local wisdom to social studies subjects in Class IV was able to improve student learning outcomes in terms of knowledge, attitudes and skills.